Association of education levels with the risk of hypertension and hypertension control: a nationwide cohort study in Chinese adults. Issue 5 (7th January 2022) - Sun, Kan; Lin, Diaozhu; Li, Mian; Mu, Yiming; Zhao, Jiajun; Liu, Chao; Bi, Yufang; Chen, Lulu; Shi, Lixin; Li, Qiang; Yang, Tao; Wan, Qin; et al.
Abstract : Background: Education attainment can improve life expectancy and guide healthy behaviours throughout an entire lifetime. A nationwide longitudinal study of the association of education status with the risk of hypertension and its control in China is lacking. Methods: The China Cardiometabolic Disease and Cancer Cohort Study is a multicentre, population-based, prospective cohort study. We performed the baseline survey from 2011 to 2012. A follow-up visit was conducted during 2014–2016. 101 959 subjects were included in the final data analyses. Cox proportional hazards regression was used to examine the associations of education levels with the risk of hypertension and uncontrolled hypertension. Results: During follow-up, 11 189 (19.9%) participants had developed hypertension among subjects without hypertension at baseline. Among the participants with hypertension at baseline, only 40.6% had controlled hypertension. Compared with the participants' education level at elementary school and below, the multivariable-adjusted HR for incident hypertension was 0.76 (95% CI, 0.72 to 0.80) in those with a middle school education level and 0.67 (95% CI, 0.63 to 0.70) in those with a high school degree or above. Correspondingly, multivariable-adjusted HRs associated with uncontrolled hypertension were 0.90 (95% CI, 0.87 to 0.92) in participants with a middle school education level and 0.85 (95% CI, 0.82 to 0.88) in participants with a high school degree or above level. Conclusion: Participants with education attainment at elementary school and below exhibited excess risks of newly diagnosed hypertension and worse blood pressure control compared with individuals with education attainment at middle school or above.